The influence of paddles on propulsion - Toussaint, H. M.; Janssen, T.; Kluft, M. (Swimming Technique, 1989)
Highly skilled competitive swimmers (M = 6; F = 4) were tested for rate of energy expenditure, power output, work per stroke, work per unit distance, and propelling efficiency at various controlled swimming speeds over 400 m with and without paddles. Under the paddles condition power input, power output, stroke frequency and work per unit distance decreased while propelling efficiency increased (distance per stroke increased by 17% and work per stroke increased by 7%). Implication: The authors contend that the use of paddles may be a "rather specific form of strength training." That is very debatable for swimmers in this study were shown to find swimming with paddles easier than without. Practical observations acknowledge that swimmers elect to swim with paddles over free-swimming. Contrary, to the claims of the study authors, paddle training may not tax the swimmer in an increased overload fashion to produce a strength training response. As well, it might be counter-productive because of the alterations in technique, a swimmer's kinesthesis, and the energy systems used to develop propulsion.